2003
DOI: 10.1111/j.1949-8594.2003.tb18116.x
|View full text |Cite
|
Sign up to set email alerts
|

Traditional vs. Retrospective Pretests for Measuring Science Teaching Efficacy Beliefs in Preservice Teachers

Abstract: The difference in gain scores produced by traditional pretests and those produced by retrospective pretests when compared to posttest scores on the Science Teaching Efficacy Belief Instrument for preservice teachers was investigated in this study. Results indicated that gain scores using the traditional pretest produced significant improvement in one factor, but not in the other, which is congruent with most other results for this instrument found in the literature. However, gain scores produced by using retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 20 publications
(18 reference statements)
6
50
1
4
Order By: Relevance
“…Only using the conventional pretest-posttest design would have significantly reduced the level of change selfreported by participants, thereby identifying that the educational programme may have had less impact on student change than it actually had. The findings in this study, similar to a number of studies on outcomes following education programmes, indicated that students tended to overestimate their ability prior to the programme commencing (Hoogstraten 1982, Cantrell 2003. However, on completing the programme students recalibrated their perception and concluded that their preprogramme ability was not as high as originally thought.…”
Section: Discussionsupporting
confidence: 76%
“…Only using the conventional pretest-posttest design would have significantly reduced the level of change selfreported by participants, thereby identifying that the educational programme may have had less impact on student change than it actually had. The findings in this study, similar to a number of studies on outcomes following education programmes, indicated that students tended to overestimate their ability prior to the programme commencing (Hoogstraten 1982, Cantrell 2003. However, on completing the programme students recalibrated their perception and concluded that their preprogramme ability was not as high as originally thought.…”
Section: Discussionsupporting
confidence: 76%
“…Increased accuracy can be viewed as a change in the underlying metric that treatment group students used when assessing their abilities. This recalibration or response-bias shift during a treatment was demonstrated by Howard (e.g., Howard & Dailey, 1979) and more recently by Cantrell (2003). Changes in selfassessment could occur through each of the processes displayed in Figure 1: joint construction of a rubric for appraising student work may influence self-observation by focusing student attention on particular aspects of performance.…”
Section: Discussionmentioning
confidence: 82%
“…The existence of these two separate but intertwined conceptual strands has contributed to a lack of clarity about the nature of teacher efficacy (Tschannen-Moran, Woolfolk, & Hoy, 1998). As Ashton and Webb (1986) and Bandura (1997) have stated, teaching efficacy is broadly defined as a situation-specific expectation that teachers can help students learn (Cantrell, 2003).…”
Section: Teacher Self-efficacymentioning
confidence: 97%
“…Efficacy expectations influence teachers' thoughts and feelings, their choice of classroom activities, the amount of effort they are willing to expend, and their persistence in the face of obstacles (Cantrell, 2003).…”
Section: Teacher Self-efficacymentioning
confidence: 99%